Search for biological activities from an invasive shrub species rosemyrtle (Rhodomyrtus tomentosa) - IRAWAN WIJAYA KUSUMA; NURUL AINIYATI; WIWIN SUWINARTI (Smujo International, 2016)
Abstract. Kusuma IW, Ainiyati N, Suwinarti W. 2016. Search for biological activities from an invasive shrub species rose myrtle (Rhodomyrtus tomentosa). Nusantara Bioscience 8: 55-59. Research into the potential of diversity, ethnobotany and ethnopharmacology and bioactivity of Indonesia plants is essential. In continuation of our search into biologically-active substances from plant sources, the ethanol extract of fruit, leaves, twig, and stem of masisin or rose myrtle (Rhodomyrtus tomentosa) were evaluated for their antioxidant and antimicrobial properties and toxicity. Antioxidant property was evaluated by DPPH free radical scavenging activity. Antimicrobial activity was examined by agar well diffusion against Salmonella typhi, Bacillus cereus, Propionibacterium acnes, and Candida albicans. Toxicity of the plant was determined by brine shrimp lethality test. The plant ethanolic extracts showed the occurrences of flavonoid, triterpenoid, and carbohydrate in the phytochemical analysis. In the antioxidant assay, the plant extracts exhibited 90-93% of DPPH radical scavenging activity at 50 ppm. Ascorbic acid, a standard compound showed 96-98% activity at the same concentration tested. In the antimicrobial assay, the activities against B. cereus and C. albicans were displayed by the fruit and leaves of R. tomentosa with activity index (AI) of 0.42 and 0.35, respectively. Leaves, stem, twig, and fruit of the plant showed activity against S. typhi and P. acnes with AI of 0.19-0.50 in comparison to that of reference compound, chloramphenicol. In the brine shrimp lethality test, leaves and fruit showed cytotoxicity with LD50 of 43.4 and 8.5 ?g/mL. The stem and twig ethanolic extracts were shown to be cytotoxic inactive. The present results showed potential of R. tomentosa extracts as natural antioxidant, antimicrobial and cytotoxic agents.